ANALISA TERHADAP UKM SEBAGAI KEKUATAN SISTEM EKONOMI KERAKYATAN DI INDONESIA - sabil, sabil (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
Economic development in Indonesia until now tends to be influenced by two kekutan world economic system is a system of economic liberalism and shittim Socialist. We all know that in Indonesia also has a populist economic system but a populist economic system has been defeated by the economic system libral who ruled almost all countries, whereas Indonesia has long been known for the economic system based on democracy that includes taking into account the culture of the Indonesian nation. Economic Democracy is taken from the values of the Indonesian nation, democratic economic system in force since 1998 then the government was determined to implement democratic economic system by issuing a decree No.IV MPR / MPR / 1999 on Guidelines which states that Indonesia's economic system is a system of social economy. Welfare-oriented development and a wide range of discretion in favor of the interests of the people. people's economy developed in an effort to further promote the community. In other words, the concept of people's economy performed as a strategy to build more priority to the welfare of the community empowerment. people's economy can be realized by restructuring the political institutions at district level. Thus the economic development of the people's problems can not be separated from the political institutions in the District level. For it must create a political climate conducive to the economic development of the people. SMEs are the backbone is one of the activities berjalanya krakyatan economy in Indonesia, when the economic crisis hit Indonesia raksaksa firms experiencing fallout as well as many out of business, while SMEs exist at that time. Keyword : SMEs, Economic Democracy